Feasibility and safety of 1-min sit-to-stand test in acute decompensated heart failure confirmed by lung ultrasound - Zhang, Xiu; Kang, Yu; Luo, Zeruxin; Chen, Qiaowei; Yang, Mengxuan; Zeng, Jijuan; Yu, Pengming; Zhang, Qing (Frontiers in Cardiovascular Medicine, 2023)
Aim: This study innovatively proposed the one-minute sit-to-stand test (1-min STST) as an assessment tool for functional capacity in acute decompensated heart failure (ADHF), in which its feasibility and safety were investigated. Methods: This was a prospective, single-center cohort study. The 1-min STST was performed after the first 48 hours of admission when vital signs and Borg score were collected. Lung ultrasound was used to measure pulmonary oedema by B-lines before and after the test. Results: 75 patients were enrolled in the study, of whom 40% were in functional class IV on admission. The mean age was 58.3 ± 15.7 years and 40% of the patients were male. 95% patients accomplished the test and the average number of repetitions was 18 ± 7. No adverse event was recorded during or after the 1-min STST. Blood pressure, heart rate and degree of dyspnea were increased after the test (all P<0.001), while SpO2 was slightly decreased (97.0 ± 1.6 vs. 96.3 ± 2.0%, P=0.003). The degree of pulmonary oedema (χ2=8.300, P=0.081) was not significantly changed, while there was a reduction in the absolute number of B-lines [9 (3, 16) vs. 7 (3, 13), P=0.008]. Conclusions: The application of the 1-min STST in early stage of ADHF appeared to be safe and feasible, which induce neither adverse event nor pulmonary oedema. It may serve as a new tool of functional capacity assessment, as well as a reference of exercise rehabilitation.